Optimization of the Making of Virgin Coconut Oil (VCO) with the Addition of Baker Yeast (Saccharomyces cerevisiae) and Fermentation Time with VCO Inducement - Riko Adityia; Herla Rusmarilin; Lasma Nora Limbong (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Virgin Coconut Oil (VCO) is a product where the process occur high temperature. The aim of this research was to find the effect of the addition of baker yeast (Saccharomyces cerevisiae) and fermentation time on the quality of virgin coconut oil. This research was using completely randomized design with two factors, i.e. : the addition of baker yeast (Saccharomyces cerevisiae) (R) : (0,1%, 0,2%, 0,3%, and 0,4%) and fermentation time (L) : (2 hours, 3 hours, and 4 hours). The parameters analyzed were yield, moisture content, free fatty acid, peroxide, and saponification number. The results showed that the addition of baker yeast (Saccharomyces cerevisiae) had highly significant effect on yield, moisture content, free fatty acid, peroxide, and saponification number. Fermentation time had highly significant effect on yield, moisture content, free fatty acid, peroxide, and saponification number. Interaction of the two factors had highly significant effect on moisture content and peroxide. The addition of baker yeast (Saccharomyces cerevisiae) of 0,1% and fermentation time of 2 hours produced the best virgin coconut oil. Keywords : baker yeast, fermentation time, Saccharomyces cerevisiae), Virgin coconut oil